The expression of the growth hormone secretagogue receptor ligand ghrelin in normal and abnormal human pituitary and other neuroendocrine tumors. - Korbonits, M; Bustin, SA; Kojima, M; Jordan, S; Adams, E; Lowe, D; Kangawa, K; Grossman, AB (2001)
Ghrelin is a recently identified endogenous ligand of the GH secretagogue (GHS) receptor. It was originally isolated from the stomach, but has also been shown to be present in the rat hypothalamus. It is a 28-amino acid peptide with an unusual octanoylated serine 3 at the N-terminal end of the molecule, which is crucial for its biological activity. Synthetic GHSs stimulate GH release via both the hypothalamus and the pituitary, and the GHS receptor (GHS-R) has been shown by us and others to be present in the pituitary. We investigated whether ghrelin messenger ribonucleic acid (mRNA) and peptide are present in the normal human hypothalamus and in normal and adenomatous human pituitary. RNA was extracted from pituitary tissue removed at autopsy and transsphenoidal surgery (n = 62), and ghrelin and GHS-R type 1a and 1b mRNA levels were investigated using real-time RT-PCR. Both ghrelin and GHS-R mRNA were detected in all samples. Corticotroph tumors showed significantly less expression of ghrelin mRNA, whereas GHS-R mRNA levels were similar to those in normal pituitary tissue. Gonadotroph tumors showed a particularly low level of expression of GHS-R mRNA. Immunohistochemistry, using a polyclonal antibody against the C-terminal end of the ghrelin molecule, revealed positive staining in the homolog of the arcuate nucleus in the human hypothalamus and in both normal and abnormal human pituitary. Pituitary tumor ghrelin peptide content was demonstrated using two separate RIA reactions for the N-terminal and C-terminal ends of the molecule. Both forms were present in normal and abnormal pituitaries, with 5 +/- 2.5% octanoylated (active) ghrelin (mean +/- SD) present as a percentage of the total. We suggest that the presence of ghrelin mRNA and peptide in the pituitary implies that the locally synthesized hormone may have an autocrine/paracrine modulatory effect on pituitary hormone release.